The Effectiveness of the Phet-Assisted Learning Cycle 5E Model to Improve Students' Critical Thinking Skills and Science Literacy on the Topic of Sound Waves - Sukardiyono Sukardiyono; Riki Perdana; Riski Putriana; Pramudya Wahyu Pradana; Jumadi Jumadi (Postgraduate, University of Mataram, 2025)
This study aims to evaluate the effectiveness of the Learning Cycle 5E model assisted by PhET simulations in improving students’ critical thinking skills and science literacy on the topic of sound waves. A quasi-experimental design was used with three classes: an experimental class (Learning Cycle 5E + PhET), control class 1 (Learning Cycle 5E only), and control class 2 (direct instruction). Classes were randomly selected from grade XI students at SMA Negeri 1 Piyungan. Instruments consisted of a critical thinking essay test and a science literacy multiple-choice test, each covering four indicators and validated using Quest. PhET simulations (“Sound” and “Wave on a String”) were integrated from the exploration to evaluation phases. The Kruskal-Wallis test showed significant differences between groups (p = 0.001). The experimental class achieved the highest posttest scores: 90.68 (SD = ±4.8) in critical thinking and 68.92 (SD = ±6.2) in science literacy. The most significant improvements occurred in evaluating arguments and understanding science concepts. These results suggest that integrating PhET simulations into the Learning Cycle 5E model effectively enhances students’ conceptual understanding, critical thinking, and science literacy. This approach can be recommended as an alternative learning strategy in physics education, particularly for abstract and complex topics.